Highly Efficient Photoelectrochemical Water Splitting Using GaN-Nanowire Photoanode with Tungsten Sulfides - Han, Sangmoon; Noh, Siyun; Yu, Yeon-Tae; Lee, Cheul-Ro; Lee, Seoung-Ki; Kim, Jin Soo (American Chemical Society, 2020)
In the present study, we have achieved high-performance photoelectrochemical water splitting (PEC-WS) using GaN nanowires (NWs) coated with tungsten sulfide (WxS1-x) (GaN-NW-WxS1-x) as a photoanode. The measured current density and applied-bias photon-to-current efficiency were 20.38 mA/cm(2) and 13.76%, respectively. These values were much higher than those reported previously for photoanodes with any kind of III-nitride nanostructure. The amount of hydrogen gas formed was 1.01 mmol/cm(2) from 7 h PEC-WS, which was also much higher than the previously reported values. The drastic improvement in the PEC-WS performance using the GaN-NW-WxS1-x photoanode was attributed to an increase in the number of photogenerated carriers due to the highly crystalline GaN NWs, and acceleration of separation of photogenerated carriers and consequent suppression of charge recombination because of nitrogen-terminated surfaces of NWs, sulfur vacancies in WxS1-x, and type-II band alignment between NW and WxS1-x. The degree of impedance matching, evaluated from Nyquist plots, was considered to analyze charge transfer characteristics at the interface between the GaN-NW-WxS1-x photoanode and 0.5-M H2SO4 electrolyte. Considering the material system and scheme for the PEC-WS, our approach provides an efficient way to improve hydrogen evolution reaction.